Development of the device sending SMS messages to point guard of the enterprise using the magnetic contact sensor and GPRS module; Физико-технические проблемы в науке, промышленности и медицине - Gulyaev M. A. (Информационные технологии, автоматизация и системы управления, 2016)
Заглавие с экрана